2017
DOI: 10.4067/s0719-81322017000300161
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic expression of the right coronary artery in horses. Comparative description with humans, pigs and other animal species

Abstract: ABSTRACT. The objective of this research was to characterise morphologically the right coronary artery and its branches in the horse. The right coronary arteries of 120 horse hearts were perfused with semi-synthetic resin (85% Palatal GP40L; 15% styrene) and mineral red dye. The morphological and biometric characteristics of the right coronary artery and its branches (digital calibrator) were assessed. The diameter of the right coronary artery was 6.72 ± 2.58 mm. The interventricular subsinusal branch ended at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
(56 reference statements)
2
13
1
Order By: Relevance
“…The ultrasonographic diameter of the RCA measured in the present study is larger than that of the proximal diameter obtained by Gomez et al measured in isolated equine hearts (6.72 ± 2.58 mm) [1]. Those authors obtained similar measurements of the LCA (mean diameter 6.76 ± 21 mm) from the same animals [14]. The measurements presented in the current study are also larger than those reported by Thuroff et al (8.91 ± 0.11 mm) [15].…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…The ultrasonographic diameter of the RCA measured in the present study is larger than that of the proximal diameter obtained by Gomez et al measured in isolated equine hearts (6.72 ± 2.58 mm) [1]. Those authors obtained similar measurements of the LCA (mean diameter 6.76 ± 21 mm) from the same animals [14]. The measurements presented in the current study are also larger than those reported by Thuroff et al (8.91 ± 0.11 mm) [15].…”
Section: Discussioncontrasting
confidence: 81%
“…These differences may be attributed to different methodologies used to measure the vessel (in vitro measurements vs in vivo measurements), the level at which the vessel was measured and the study sample size. In addition, the authors of previous studies carried out measurements of hearts from younger horses up to 3.5 years old and weighing from 250 to 300 kg [1, 14]. The animals from the present study were older and larger.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations